COVID-19 vaccine hesitancy and GAD: The role of risk perception and vaccination status - Wang, Bin; Zhong, Xiao; Fu, Haojie; He, Mengting; Hu, Ruilin (Frontiers in Public Health, 2022)
Background and purpose As Coronavirus disease (COVID-19) continues to spread around the world, COVID-19 vaccines are the most effective weapons against the global pandemic. Yet vaccine hesitancy remains a serious problem and can pose certain hazards to individuals' mental health, such as rising anxiety. Therefore, based on Self-Discrepancy Theory, this paper aims to explore the role of COVID-19 vaccine hesitancy on individual generalized anxiety disorder and its influence mechanisms through two studies. Methods Study one involved 654 Chinese participants using the Vaccine Hesitancy Questionnaire and the Generalized Anxiety Disorder 7-item (GAD-7) scale. In Study two, the Vaccine Hesitation Questionnaire, GAD-7 scale, Perceived Risk of COVID-19 pandemic scale, and Vaccination Status Questionnaire were used and data from 3,282 Chinese residents was collected. Results Vaccine hesitancy directly increases generalized anxiety disorder; risk perception plays a partial mediating role between vaccine hesitancy and generalized anxiety disorder; vaccination status moderated vaccine hesitancy's effect on risk perception and generalized anxiety disorder. Conclusion Vaccine hesitancy predicts generalized anxiety disorder through risk perception, but the mediating role of risk perception is moderated by vaccination status, which means that for the vaccinated group when their vaccine hesitancy is reduced, it will be easier to reduce the risk perception and thus the generalized anxiety disorder.